Pengendalian Pencoklatan Produk Hasil Restrukturisasi Bubur - Sri Raharjo; Suparmo Suparmo; Wahyu Supartono; Zaki Utama (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2002)
Upon peeling and slicing fresh fruits are easily discolored due to enzymatic reaction in the presence of oxygen. Restructured fruit also suffer the discoloration during aerobic storage either at room temperature or under refrigeration. The objective of this study was to find alternatives for preventing or retarding the discoloration rate of calcium-alginate restructured fruits during aerobic refrigerated storage using anti browning additives. Four different fruits including avocado, mango, jack fruit, and soursop were restructured using sodium alginate (1% w/w) and calcium lactate (1% w/w). The additives tested were citric acid 0.5% (w/w), ascorbic acid 0.05% (w/w), sodium disulfite 0.01% (w/w), N-acetyl-cysteine 0.05% (w/w), and combination of citric acid 0.05% (w/w) and N-acetyl-cysteine 0.05% (w/w). Addition of anti browning additives at the specified concentration was effective in delaying the discoloration of restructured fruits during aerobic storage at 4ºC for up to 6 days. Among the additives tested the use of combination of citric acid 0.05% (w/w) and N-acetyl-cysteine 0.05% (w/w) was the most effective in retarding the discoloration across the fruits. Restructured soursop, in particular, was not undergoing significant sidcoloration for 11 days of refrigerated storage.